Niepowtarzalne doświadczenie świata (O Stanisławie Jaworskim – wspomnienia i lektury) - Ligęza, Wojciech (Przestrzenie Teorii, 2019)
This article is composed of three main parts: the first part briefly presents Prof. Jaworski’s professional and creative accomplishments, the second part provides a description of the most important research questions addressed by Prof. Jaworski in his scholarly work, while the last section of the article is devoted to personal recollections by the present writer, highlighting the profiles and roles of Professor Jaworski as a lecturer, scholar, intellectual, editor, science organiser and discourse partner. Stanisław Jaworski was a prominent expert in the Kraków Avantgarde group and the subsequent history of this avant-garde movement in Polish poetry in Poland as well as on changes and literary recurrences in modern Polish and European literature. His literary research techniques include a comparative perspective as an important element, whereas interpretations of poems still play a substantial part. Prof. Jaworski has written a groundbreaking work Piszę, więc jestem? [I write therefore I am?] introducing new ideas and methods in genetic criticism, the approach to the study of literature Prof.Jaworski adopted and developed. The present article identifies common ideas and ways of thinking in research and poetical creative work.